الطب الشرعي ودوره في الإثبات الجنائي - بونعناع، محمد (رضوان العنبي, 2022)
معلوم أن القضاء الجنائي يهتم بتحقيق العدالة وإرجاع الحقوق لذويها عبر مر العصور والأزمنة، ونظرا للتطور الحاصل في مجال الجريمة وتعدد أشكالها وألوانها وصعوبة تحديد حيثياتها بوسائل تقليدية، بادر المتخصصون في العلوم المختلفة إلى البحث عن سبل حل القضايا الشائكة واستثمار تلك العلوم للحد والتضييق على الجريمة خدمة للعدالة وصونا للحقوق والحريات، ولما كانت الجريمة مسألة محتومة في مختلف المجتمعات مواكبة للتطور البشري وتقدمه في مختلف المجالات والأصعدة كان الحد منها إحدى المشكلات الرئيسة للدول والأفراد، حيث تسعى الدول إلى الحد منها والتخفيف من آثارها من خلال تحقيق الأمن وتوفير الأمان والطمأنينة للأفراد والجماعات حفاظا على سلامة أرواحهم وأمنا لحياتهم وضمانا لحقهم في الحياة فبادر المتخصصون إلى إيجاد بدائل أكثر نجاعة لتطويق الجريمة والحد من انتشارها، فبرزت علوم أخرى فرضها التطور الحاصل في الجريمة ومنها الطب الشرعي أو ما يطلق عليه بالطب العدلي باعتباره علما من العلوم الطبية المتخصصة وما يتعلق به من فروع الطب الأخرى. It is known that the criminal justice is concerned with achieving justice and restoring rights to their owners through the ages and times, and in view of the development taking place in the field of crime and the multiplicity of its forms and colors and the difficulty of determining its merits by traditional means, specialists in various sciences took the initiative to search for ways to solve thorny issues and invest those sciences to limit and restrict crime in the service of justice and the preservation of rights and freedoms Since crime is an inevitable issue in various societies, keeping pace with human development and its progress in various fields and levels, limiting it is one of the main problems for states and individuals, as states seek to reduce it and mitigate its effects by achieving security and providing safety and reassurance to individuals and groups in order to preserve the safety of their lives, security for their lives and a guarantee They caught their right to life, so specialists took the initiative to find more effective alternatives to cordon off crime and limit its spread. Other sciences imposed by the development in crime emerged, including forensic medicine or what is called forensic medicine as one of the specialized medical sciences and other related branches of medicine
Keywords: الطب الشرعي -- القضاء الجنائي -- العدالة الجنائية -- التشريع المغربي